2019
DOI: 10.1002/jmv.25548
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ lymphocytes but not B lymphocytes are required for protection against chronic hepatitis E virus infection in chickens

Abstract: Hepatitis E is an important global disease, causing outbreaks of acute hepatitis in many developing countries and sporadic cases in industrialized countries. Hepatitis E virus (HEV) infection typically causes self-limiting acute hepatitis but can also progress to chronic disease in immunocompromised individuals. The immune response necessary for the prevention of chronic infection is T cell-dependent; however, the arm of cellular immunity responsible for this protection is not currently known. To investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…These observations in the human setting are in agreement with recent data from the chicken as well as rhesus macaque HEV infection models that indicated an important role of HEV-specific CD8+ T cells in viral clearance. 3,4 The number of HEV-specific T-cell responses correlated negatively with viral load as well as ALT levels in chronic HEV infection (Fig. S4C,D).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These observations in the human setting are in agreement with recent data from the chicken as well as rhesus macaque HEV infection models that indicated an important role of HEV-specific CD8+ T cells in viral clearance. 3,4 The number of HEV-specific T-cell responses correlated negatively with viral load as well as ALT levels in chronic HEV infection (Fig. S4C,D).…”
Section: Discussionmentioning
confidence: 93%
“…Recent in vivo evidence from 2 animal models (chicken and rhesus macaque) demonstrates an important role of HEV-specific CD8+ T cells in HEV control. 3,4 However, in humans, there is still a paucity of data on HEV-specific CD8+ T-cell immunity. 5 Studies using recombinant HEV capsid protein (corresponding to open reading frame [ORF] 2) as well as overlapping peptides covering some or all HEV domains (ORF1-3) showed broad and vigorous HEV-specific CD8+ T-cell responses in immunocompetent patients with acute infection that contracted upon resolution of infection.…”
Section: Introductionmentioning
confidence: 99%
“…9 Although recent studies suggested HEV clearance depends on an effective virus-specific CD8+ T-cell response, there is a remarkable deficit in knowledge about the contribution of adaptive T-cell immunity to the control and pathogenesis of HEV infection. 10,11 In particular, little information is currently available about the abundance, phenotype, functional capacity and fate of pre-existing and induced HEV-specific CD8+ T cells, which might determine the divergent outcomes of infection.…”
mentioning
confidence: 99%